Sick building syndrome and perceived indoor environmental quality: A survey of apartment buildings in Hong Kong - Wong, Siu-Kei (Habitat Int, 2009)
The outbreak of a highly communicable disease, SARS, in Asia in 2003 has revealed the health risk of living in a high-density environment. To show the important connection between human health and environmental quality, this study surveys the prevalence of sick building syndrome (SBS) among apartment residents and their evaluation of indoor environmental quality (IEQ). Based on a sample of 748 households living in Hong Kong, two interesting findings are revealed: (1) nasal discomfort was the commonest home-related SBS symptom despite the absence of any central ventilation system in apartment buildings; (2) noise, rather than ventilation, was the major IEQ problem perceived by residents. Our statistical analysis further showed that residents with SBS symptoms were less satisfied with their IEQ than those without. That is, despite a positive evaluation of specific IEQ criteria with respect to the building residents lived in, if they reported feeling SBS related symptoms, the overall IEQ evaluation of their building could still be negative. This perception bias gives rise to a sample selection problem in measuring perceived IEQ, which has implications on housing management practices and the formulation of a healthy housing policy.